Mengurangi Risiko Jatuh pada Lanjut Usia dengan Latihan Keseimbangan - Widagdo, The Maria Meiwati; Sambudi, Rambat (Universitas HKBP Nommensen, 2021)
Background: Population of elderly in Indonesia continues to grow. Physical changes in the elderly cause balance disturbances, increasing the risks of falling. Objective: To determine balance training effectiveness on reducing risks of falls in elderly. Methods: This study used a quasi-experimental design with control and intervention groups. Functional Reach Test (FRT) and Falls Efficacy Scale-International (FES-I) were used to assess balance function. The elderly in this study had risks of falling according to FRT and FES-I. Timed Get-up and Go Test was used to assess physical function. Education and balance exercises were given for 3 weeks to the intervention group. Pre-test data were taken at the beginning of the study, while post-test data after the balance training was given to the intervention group. Paired t-test was used to compare the pre-test and post-test data. Results: Research was conducted in Warungboto and Giwangan Kampongs, Umbulharjo District, Yogyakarta Municipality. Data from 60 elderly: 30 in the intervention and 30 in the control groups. Paired t-test showed a significant difference between pre-test and post-test results in the intervention group on FRT (t=-16,301, p<0.001, and FES-I (t=-24,457, p<0.001). The three-week-balance-training significantly reduced the risk of falling in the intervention group. Significant difference was not found in the control group on FRT (t=-0.126, p=0.901), and FES-I (t=-0.764, p=0.451). There was no significant reduction in the risks of falls in the control group. Conclusion: Balance training is effective in reducing the risk of falls in elderly.